Octreotide protects ovary against ischemia–reperfusion injury in rats: Evaluation of histological and biochemical parameters. Issue 10 (30th July 2015) - Yildirim, Nuri; Yigitturk, Gurkan; Sahingoz Yildirim, Alkim Gulsah; Akdemir, Ali; İlgen, Orkun; Yeniel, Ozgur; Ergenoglu, Mete; Erbas, Oytun
Abstract Aim This study investigated the efficacy of octreotide for prevention of ischemia–reperfusion injury in rat ovary. Methods Thirty‐two adult female rats were included. Rats were divided into five groups: in the sham group, the abdominal wall was only opened and closed; in the torsion group, ischemia was induced for 3 h using a torsion model involving atraumatic vascular clips; in the torsion/octreotide group, rats were given 100 µg/kg i.p. octreotide 30 min before torsion was induced; in the torsion/detorsion group, rats underwent 3 h ischemia–3 h reperfusion; in the torsion/detorsion/octreotide group, rats underwent 3 h ischemia followed by 100 µg/kg octreotide i.p. 30 min prior to 3 h reperfusion. Ovarian tissue damage was scored on histopathology. Ovarian tissue malondialdehyde and plasma pentraxin 3 were measured biochemically. Results In comparison with the sham group, both the torsion and torsion/detorsion groups had significantly higher scores for follicular degeneration, vascular congestion, edema, hemorrhage and leukocyte infiltration. Octreotide significantly decreased these scores in both groups. Ovarian malondialdehyde and plasma pentraxin 3 were significantly higher both in the torsion and torsion/detorsion groups compared with the sham group. Octreotide also decreased these levels significantly both in the torsion/octreotide and torsion/detorsion/octreotide groups. Conclusion Octreotide ameliorated the potential side‐effects of ovarian ischemia–reperfusion injury in a rat model.